4-H Engineering Design Challenge Program: Engaging Youth in STEM Learning - R.Michael Compton; Rebecca L. Meyer; Anne Stevenson; Somongkol Teng ([TEST] Journal of Extension, 2021)
The University of Minnesota 4-H Engineering Design Challenge program is an experiential learning opportunity in which youth work with adult volunteers to create Rube Goldberg influenced machines to address real-world issues. The program components are designed to help youth develop STEM work skills using an Engineering Design Process, increase interest in STEM content knowledge, and explore STEM career interests/aspirations. Evaluation indicates a majority of participants learn the engineering design process, principles of mechanical engineering, teamwork, public speaking, and problem solving. Programmatic outcomes and supports provide for the successful replication, adaptation, and implementation in both formal and non-formal learning environments.
Keywords: 4-H; Engineering Design Process; STEM; youth development